Climate Change Mitigation With Renewable Energy: Geothermal - Baba, Alper; Baba, Alper (Springer Verlag, 2011)
On a global scale, there is increasing evidence that climate is changing and of a discernible human influence. Many of scientists are confident that if current emissions of greenhouse gases continue, the world will be warmer, sea levels will rise and regional climate patterns will change. According to some scientist, global temperatures are expected to rise faster over the next century than over any time during the last 10,000 years. From this token, geothermal energy is now considered to be one of the most important alternative energy sources to minimize climate change. Geothermal technologies for power generation or direct use operate with little or no greenhouse gas emissions. Geothermal energy is generally accepted as being an environmentally-friendly energy source, particularly when compared to fossil fuel energy sources. Geothermal resources have long been used for direct heat extraction for district urban heating, industrial processing, domestic water and space heating, leisure and balneotherapy applications. Geothermal energy is used in more than 80 countries for direct heat application and 24 countries for power generation. Re-injection of fluids maintains a constant pressure in the reservoir, thus increasing the field's life and reducing concerns about environmental impacts. Geothermal energy has several significant characteristics that make it suitable for climate change mitigation.
Keywords: Geothermal energy; Renewable energy sources; Environment; Climate change